Techno-economics of Optical Access Network Sharing - AFRAZ, NIMA (Trinity College Dublin. School of Computer Science & Statistics. Discipline of Computer Science, 2020)
Several parallel trends, including the growing number of Internet reliant devices/services, increasing Internet penetration rates, and the continuing popularity of bandwidth-hungry multimedia content contribute to the exponential surge of Internet traffic. The combination of these trends could imply a considerable increase in network infrastructure investment for the telecom and broadband operators. In addition, the high cost of initial investment could escalate the market barriers to entry for the innovative service providers incapable of deploying their own network infrastructure. In this dissertation, we explore if and how enabling optical access network sharing could cultivate new network ownership and business models that simultaneously keep the end-user subscription fees low and facilitate the market entry for the smaller service providers. We aim to identify and address the technological and economic barriers of optical access network sharing. The broad scope of this dissertation concerns the inter-operator sharing of optical access networks which connect the end-users to the operators' network in the last-mile. The access segment of the communications network is recognized to be the most costly due to its deployment scale. Therefore, a reduction in cost in the access will have a multi-fold impact on the overall capital expenditure for network deployments. The dissertation focuses in particular on PONs as the most widespread type of optical access networks. The central argument of the present research is that network infrastructure/resource sharing has the potential to reduce the capital and operational expenditure of the network operators. This will allow for more competition as the market entrance cost decreases. We first address the lack of tenant operators' adequate control over the shared resources in a multi-tenant PON as a technological barrier. We provide a solution to strengthen the network operators' control over their share of the network in a multi-tenant PON. This is made possible by allowing the operators to schedule the transmission over the network using tailored algorithms to meet their requirements (e.g., latency and throughput). The dissertation argues that providing a virtual (software) instance of the DBA algorithm as opposed to the inflexible hardware implementation first enables the coexistence of various services on the PON and second, improves the overall utilization of the network capacity. While the virtualization of the DBA removes the technical barrier for the inter-operator resource sharing, it does not come with a natural incentive for the operators to share their resources with competitors. Therefore we tackle the lack of incentive for sharing excess network capacity in PON by providing monetary compensation in return for sharing. We model the multi-tenant optical access network with multiple coexisting operators as a market where they can exchange their excess capacity. We propose a sealed-bid multi-item double auction to enable capacity trading between the network operators. Through mathematical proof and market simulation/visualization, we prove that the proposed auction mechanism meets the essential requirements for an economic robust market mechanism (e.g., incentive compatibility, individual rationality, and budget balance). This provides trusted market conduct in the presence of a central authority (e.g., the public infrastructure provider) that all the operators trust.
APPROVED